Treatment with flexible endoscopy of Zenker’s diverticulum: an effective and safe technique - González, Nicolás; Viola, Marcelo; Méndez, Arturo; Taullard, Andrés; Gentile, Mariana; Gamba, Alejandra; Debenedetti, Dardo; Duarte, Adrián; Canessa, César (Cirugía del Uruguay, 2019)
Background: Treatment of Zenker's diverticulum (DZ) has evolved from open surgery to flexible endoscopy, resulting in lower morbidity and mortality. The endoscopic treatment consists of the cricopharyngealmyotomy using multiple devices. Aim: The purpose of this study is to show a therapeutic alternative for flexible endoscopy for Zenker's diverticulum, using different cutting instruments. Methods: We describe a series of cases of patients diagnosed with Zenker's diverticulum treated by endoscopy, between March 2014 and July 2018. Allprocedures were performed by a single endoscopist. Data from endoscopic records werecollected retrospectively and demographic variables, symptoms, technical aspects, complications and follow-up were analyzed. Results: 12 patients were included, 7 (58%) female, mean age 69 years (range: 53-90). All patients had dysphagia for solids and liquids, 2 patients also had respiratory symptoms. The average size of the diverticula was 3.6 cm. The myotomy was performed with LigaSure in 4 patients, with clutch-cutter in 3 and needle knife in 5 cases. In 11 (91.6%) cases, symptom improvement was obtained, 2 (16%) patients presented recurrence of symptoms during a median follow-up of 9 months. One case (8%) required endoscopoicreintervention to obtain relief of dysphagia. Microperforationwas presented in one patient (8%), which resolved with conservative treatment. Conclusions:Diverticulotomy through flexible endoscopy was effective and safe for the treatment of DZ, so it should be considered in the therapeutic arsenal of this pathology.